2022
DOI: 10.1108/aaaj-10-2019-4220
|View full text |Cite
|
Sign up to set email alerts
|

Accountability and governance in implementing the Sustainable Development Goals in a developing country context: evidence from Tanzania

Abstract: PurposeThis paper examines the accountability and governance mechanisms and the challenges in a multi-stakeholder partnership seeking to implement the Sustainable Development Goals (SDGs) in a developing country (DC), namely Tanzania.Design/methodology/approachThe paper draws on work on the shift from government to governance to meta-governance to examine the SDGs framework's governance regime. The data stems from documentation, focussed group discussions and face-to-face interviews with key stakeholders invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 84 publications
0
13
0
3
Order By: Relevance
“…Governments' roles and the way they choose to act (or not) in society are not disconnected from the political dimension, with variations in governance styles depending on the convergence between politics and policy. Whether elected officials, autocrats, or state bureaucracies, political leadership is an essential attribute, which shows that the connections between politics and policy depend on patterns of interaction between governments and society (Lauwo et al, 2022) to define the governance style. The governance theory can gain more analytical strength if it understands how hierarchies, markets, and networks act to design policies considering the political regime's dynamics (which can be pluralist or populist) and the bureaucracies' political dynamics (which can be interactive or noninteractive with society).…”
Section: Discussionmentioning
confidence: 99%
“…Governments' roles and the way they choose to act (or not) in society are not disconnected from the political dimension, with variations in governance styles depending on the convergence between politics and policy. Whether elected officials, autocrats, or state bureaucracies, political leadership is an essential attribute, which shows that the connections between politics and policy depend on patterns of interaction between governments and society (Lauwo et al, 2022) to define the governance style. The governance theory can gain more analytical strength if it understands how hierarchies, markets, and networks act to design policies considering the political regime's dynamics (which can be pluralist or populist) and the bureaucracies' political dynamics (which can be interactive or noninteractive with society).…”
Section: Discussionmentioning
confidence: 99%
“…Sin duda el esfuerzo de las administraciones para llegar a esta meta forma parte de su cooperación con la sostenibilidad y requiere una rendición de cuentas a los ciudadanos sobre dichas acciones (Agliata et al, 2022), la cual es fundamental para la buena gobernanza (Bowen et al, 2017;Lauwo et al, 2022). Por eso, las administraciones han comenzado a proporcionar información sobre el cumplimiento de los ods.…”
Section: La Información Sobre Contribución a Los Ods En Las Administr...unclassified
“…Guerrero-Gómez et al (2021) analizan una muestra de gobiernos locales en América Latina, evidenciando que algunos factores, como el tamaño de la población, el nivel educativo, el desempleo, la calidad de la legislación y la corrupción política, influyen en la transparencia relacionada con el cumplimiento de los ods. Lauwo et al (2022) examinan cómo se han implementado los ods en Tanzania, considerando en particular los mecanismos de gobernanza y rendición de cuentas, y revelan que las estructuras verticales formales han creado un entorno difícil para las colaboraciones de múltiples partes interesadas y han sido un obstáculo para la localización de la rendición de cuentas. Además, señalan que la falta de sistemas de reporte y rendición de cuentas ha limitado la implementación de los ods en el país.…”
Section: La Información Sobre Contribución a Los Ods En Las Administr...unclassified
See 1 more Smart Citation
“…Although most of the examples in this section are from EU countries, the non-normative definitions of the analytical and design concepts of governance, governance frameworks and metagovernance make them a good basis for tailor-made application in many different national political-administrative cultures and traditions, as research has shown. Metagovernance has been analyzed in Australia (Eberhard, 2018), Canada (Doberstein, 2013), China (Li, Homburg, de Jong, and Koppenjan, 2016), Colombia (Bonivento, 2014), Kenya (Beisheim et al, 2018), Nigeria (Agu, Okeke, and Idike, 2014), Tanzania (Lauwo, Azure, and Hopper, 2022), and The Netherlands (Hooge, Waslander, and Theisens, 2021), for example. In addition, there are examples of comparative research using a metagovernance lens on Germany, the Netherlands, Australia, China, and South Africa (Pahl-Wostl, 2019), on Chile, China, Denmark, Netherlands, Portugal, and Vietnam (Monteiro, do Rosário Partidário and Meuleman, 2018), and England, The Netherlands and Germany (Meuleman, 2008).…”
Section: Conceptual Frameworkmentioning
confidence: 99%